HOW IS MEDICAL TOURISM DEVELOPING IN OUR COUNTRY? - Ibragimov T. T. (Modern American Journals, 2025)
The article discusses the practical work being carried out by relevant ministries, committees, agencies, associations, departments, state and non-governmental organizations on the further development of medical and health tourism in accordance with the Resolution of the President of the Republic of Uzbekistan No. PQ-335 dated September 23, 2024 “On additional measures for the further development of medical and health tourism in the Republic of Uzbekistan”. The results of additional measures aimed at state support and increasing the export potential of business entities in operating medical institutions are analyzed. In accordance with it, the service program in the field of medical tourism, as well as the results of monitoring the quality of services provided by medical institutions and sanatoriums and boarding houses, the activities of medical tourism clusters, the results achieved in developing and constantly promoting the medical and health tourism brand, the establishment of sanatoriums of the category (star) hotel type and the introduction of a system of their certification, and other issues planned to be implemented within the framework of state programs are analyzed.
Keywords: Uzbekistan, medicine, tourism, medical and health tourism, health care, foreign patients, quality of services, export activities, financial assistance, sanatorium-resort zones, mountainous, healing mud layers, healing waters, sanitation, water (thermal water), sanatorium-resort zones